Toward an understanding of the molecular level properties of ziegler-natta catalyst support with and without the internal electron donor - Thushara, K. S.; Gnanakumar, Edwin S.; Mathew, Renny; Jha, Ratnesh Kumar; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Sarma, Krishna; Padmanabhan, Sudhakar; Bhaduri, Sumit; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2011)
Two Ziegler-Natta catalysts supported on molecular adducts, namely, MgCl2 center dot 6EtOH (ME) and MgCl2 center dot 5EtOH center dot EtOOCPh (Est-ME), have been prepared. A systematic effort has been made to unravel the molecular level structure property relationships of the catalysts and adducts. Ethylbenzoate is an internal electron donor, and its in situ formation through EtOH+PhCOCl coupling is successfully achieved. The above adduct has been treated with TiCl4, and the resultant catalyst (Ti/Est-ME) is evaluated for ethylene polymerization activity. Rand C-13 CP/MAS NMR of Est-ME (Ti/Est-ME) show carbonyl features at 1730 (1680) cm(-1) and 169 (170) delta, respectively, providing direct support for the presence of ester as an integral part. In spite of low surface area, Ti/Est-ME gives higher yield for ethylene polymerization than the one derived from ME. The results indicate that electronic environment is more important than surface area or any other single factor in determining the polymerization activity.